Technology Entrepreneurship Project (ENT 600) : Coach IP Holdings LLC / Nuraina Aqilah Ismail - Ismail, Nuraina Aqilah (2021)
An entrepreneur is an individual who starts and runs a business with limited resources and planning, and is responsible for all the risks and rewards of his or her business venture. The business idea usually encompasses a new product or service rather than an existing business model. Through this case study, I have the opportunity to identify and study on how Coach IP Holdings LLC runs the business from several aspects such as marketing strategy, organizational structure, operational strategy and also the products or services provided by this renowned company. This company succeeds to confront with the ups and downs in business during their journey towards success. They always put so much effort to prioritise the customers’ satisfaction towards their products. Field Tote 40 in Colourblock with Coach Badge is the most well-known product released by Coach IP Holdings LLC. This is a luxury handbag that cost MYR 3,200 with soft polished pebble leather, inside zip pocket, detachable strap with 60cm drop for shoulder or crossbody wear and it fits a 38cm laptop. However, there are several problems that I had found out regarding this costly handbag. Field Tote 40 in Colourblock with Coach Badge has low level of security, lacks of interior compartment, not up-to-date design and also it is a leather handbag which contributes to the expensive price of this handbag. From the problems identified, there are several recommended best solutions for the improvement of the existing product which are implementing a wireless anti-snatch device, designing multiple-compartmented handbag, applying trending colours that are universal for both women and teens on the handbag such as flame scarlet, chive (green) and saffron (blue), replacing leather to canvas as the main material to manufacture the new version of upgraded product. In short, we must create a fashionable and sophisticated handbag which can provide a great satisfaction to the all customers especially women and teens.